Hubungan status imunisasi dasar dan berat badan lahir dengan kejadian ISPA pada balita - Mayesti, Freya Ekklesia; Arifin, Syamsul; Trisia, Adelgrit; Widodo, Tri; Carmelita, Austin Bertilova (Barigas: Jurnal Riset Mahasiswa, 2024)
Acute Respiratory Infection (ARI) is a health problem that affects the human respiratory system. This study aims to determine the relationship between Basic Immunization Status and Birth Weight with the incidence of ARI in toddlers in the work area of UPT Puskesmas Kurun, Gunung Mas Regency July-September 2023. This study used a type of non-experimental research: Observational analytic, with case control method, with Chi Square statistical test, considering the significance value (p), Odds Ratio (OR), and Confidence Interval (CI) value of 95% or α = 0.05. The results of the Chi square test showed that there was a significant relationship between immunization status and the incidence of ARI among children under five (p-value 0.032). The results of the OR calculation showed that respondents with incomplete basic immunization status were 4,000 times more likely to experience ARI than those with a complete immunization history (95% CI = 1,250-12,804). Chi square test results showed there was a significant relationship between birth weight and the incidence of ARI among children under five (p-value 0.046). The results of the OR calculation showed that respondents with a history of LBW were 4.043 times more likely to experience ARI than those without LBW (95% CI = 1.154-14.164). There is a relationship between basic immunization status and birth weight with the incidence of ARI in toddlers in the working area of UPT Puskesmas Kurun, Gunung Mas Regency.